1976
DOI: 10.1037/0033-2909.83.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Estimating coefficients in linear models: It don't make no nevermind.

Abstract: It is proved that under very general circumstances coefficients in multiple regression models can be replaced with equal weights with almost no loss in accuracy on the original data sample. It is then shown that these equal weights will have greater robustness than least squares regression coefficients. The implications for problems of prediction are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
351
3
2

Year Published

1978
1978
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 623 publications
(367 citation statements)
references
References 7 publications
11
351
3
2
Order By: Relevance
“…The summary statistics for these three models are very similar, illustrating that the multiple regression model is not sensitive to small variations in the weights chosen (cf. Wainer, 1976). In fact, the regression model with the weights set by the CAC has the best correlation with human scores for sets of three tasks.…”
Section: Resultsmentioning
confidence: 91%
“…The summary statistics for these three models are very similar, illustrating that the multiple regression model is not sensitive to small variations in the weights chosen (cf. Wainer, 1976). In fact, the regression model with the weights set by the CAC has the best correlation with human scores for sets of three tasks.…”
Section: Resultsmentioning
confidence: 91%
“…The ways in which outputs are relatively insensitive to changes in coefficients (provided changes in sign are not involved) have been investigated most recently by Green (1977), Because each of the random models is positively correlated with the criterion, the correlation of their average, which is the unit-weighted model, is higher than the average of the correlations. Wainer (1976), Wainer and Thissen (1976), W. M. Edwards (1978), and Gardiner and Edwards (197S). Dawes and Corrigan (1974, p. 105) concluded that "the whole trick is to know what variables to look at and then know how to add."…”
Section: Paul Meehps (1954) Book Clinical Versus Statistical Predictimentioning
confidence: 99%
“…The fact that linear (or almost linear) regression models human decision-making quite well is also well known. It was reported by decisionmaking researchers during the Seventies (Dawes, 1974;Wainer, 1976). Furthermore, machine learning models have been often shown to be more accurate then well established statistical techniques (Tarn, 1992;Thrun et al, 1991), in particular, when compared with various regression models.…”
Section: Discussionmentioning
confidence: 99%